An immuno polymerase chain reaction screen for the detection of CJC‐1295 and other growth‐hormone‐releasing hormone analogs in equine plasma. Issue 6 (25th December 2018) - Timms, Mark; Ganio, Katherine; Forbes, Grace; Bailey, Simon; Steel, Rohan
Abstract: CJC‐1295 is a 30 amino acid peptide‐based drug that stimulates the release of growth hormone (GH) from the pituitary gland. It is unique among performance‐enhancing peptides due to the presence of a reactive maleimidopropionic acid group that covalently links the peptide to free thiols on the surface of plasma proteins. Once conjugated, CJC‐1295 remains active in the bloodstream for significantly longer than non‐conjugated peptide‐based drugs that are rapidly excreted. Conjugation of CJC‐1295 to plasma proteins prevents its detection by top‐down mass‐spectrometry‐based peptide screening protocols as it effectively becomes a macromolecular protein with an undefined molecular weight. Using a pair of monoclonal antibodies raised against the CJC‐1295 peptide, we present an immuno‐polymerase chain reaction (I‐PCR) assay that is capable of detecting the CJC‐1295‐protein conjugate at concentrations down to 0.8 pg/mL. Detection of endogenous equine GHRH necessitated a screening threshold for CJC‐1295 in equine plasma of 50 pg/mL. The effectiveness of the assay for controlling the illicit use of CJC‐1295 was confirmed in equine blood samples after administration in thoroughbred race horses. Abstract : CJC‐1295 is a peptide drug that stimulates the production of growth hormone (GH). Compared to other Growth Hormone Releasing Hormone analogues, CJC‐1295 has an extended half‐life due to a maleimidopropionic acid group that chemically links the peptide to plasma proteins. As a result, CJC‐1295 behaves more like a protein doping agent than a peptide based drug. Using monoclonal antibodies raised against the CJC‐1295 peptide, a real time Immuno‐Polymerase Chain Reaction (I‐PCR) assay is presented to detect the CJC‐1295 protein conjugates.